The Effect of Effleurage Massage Using Lavender Oil on the Sleep Quality of Third Trimester Pregnant Women - Ika Putri Af’idatun Nisa’; Sri Winarni; Susanti Pratamaningtyas; Indah Rahmaningtyas (Akademi Keperawatan Yarsi Samarinda, 2026)
Sleep quality disorders are one of the complaints often experienced by pregnant women in the third trimester due to physiological changes, physical discomfort, and psychological changes that occur during pregnancy. One non-pharmacological intervention that can be used to tackle this problem is effleurage massage using lavender oil, which has a relaxation effect through touch stimulation and aromatherapy. This study aims to determine the effect of Effleurage Massage using lavender oil on the sleep quality of third-trimester pregnant women in the working area of Sukorame Health Center, Kediri City. Used a pre-experimental design a one-group pretest-posttest design approach. The study sample consisted of 30 third-trimester pregnant women selected using accidental sampling technique according to inclusion and exclusion criteria. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality before and after the intervention. Intervention in three sessions via home visits. Data were analyzed using the Wilcoxon Signed Rank Test. Before the intervention, most respondents had poor to very poor sleep quality after the intervention, 27 respondents (90%) reported an improvement to good sleep quality. The average PSQI score decreased from 9.87 to 6.33, and the statistical test results showed an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a significant effect of effleurage massage using lavender oil on the sleep quality of pregnant women in their third trimester. Future research is recommended to employ a design with a control group, a larger sample size, and measurements of psychological and environmental factors to enhance the validity of the research findings.